2017
DOI: 10.1016/j.rser.2016.11.090
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the diffusion of domestic biogas technologies. Systematic conceptualisation of existing evidence from developing and emerging countries

Abstract: Accelerating the diffusion of domestic biogas is considered to be a promising option for reaching the goal of universal access to energy by 2030, particularly for the provision of cooking energy for rural populations in developing countries. The aim of this study is to develop a systematic account of the factors that influence the diffusion of domestic biogas technologies. To achieve this objective, a three step analysis approach is applied. In the first step, a conceptual model is built based on insights from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 39 publications
1
11
0
2
Order By: Relevance
“…These results agree with those presented in [23,34]. Taking into account the high percentage of CH 4 obtained with the amine MEA, the CO 2 loads in the rich and lean amine streams, and the lower presence of H 2 O in the sweet gas obtained, we decided to dehydrate the obtained gas with TEG. The goal was to obtain a drier landfill gas that would meet the different quality restrictions for use [11], such as a CH 4 concentration greater than 90 %, a total concentration of gases (e.g., .…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…These results agree with those presented in [23,34]. Taking into account the high percentage of CH 4 obtained with the amine MEA, the CO 2 loads in the rich and lean amine streams, and the lower presence of H 2 O in the sweet gas obtained, we decided to dehydrate the obtained gas with TEG. The goal was to obtain a drier landfill gas that would meet the different quality restrictions for use [11], such as a CH 4 concentration greater than 90 %, a total concentration of gases (e.g., .…”
Section: Resultssupporting
confidence: 86%
“…Each deacidification process was carried out for the conditions of biogas generated in the landfill "El Carrasco" in Bucaramanga, Colombia. The results showed that the use of amines for biogas cleaning produces a significant enrichment of the landfill biogas, obtaining percentages of CH 4 of up to 90 % from a biogas with 57.3 % CH 4 . Likewise, as this enrichment is obtained, mainly at the expense of CO 2 removal, these processes may be suitable for the use of renewable sources of energy with lower emission rates of greenhouse gases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…China's government subsidy is reconsidered in this work, resulting in the recommendation that subsidy should be based on products (i.e., output-oriented) instead of only input subsidy for construction. The policy could focus on the revival of abandoned biogas plants as well.Sustainability 2020, 12, 1490 2 of 21 effectively and widely implemented in countries where governments and institutions are involved in the subsidy, planning, design, construction, operation, and maintenance of biogas plants [7,8]. A number of countries in Asia and Africa have launched massive campaigns to popularize biogas technology via government support and international aid (Table 1) [9,10].…”
mentioning
confidence: 99%